2018
DOI: 10.3389/fmicb.2018.00721
|View full text |Cite
|
Sign up to set email alerts
|

Novel Polymyxin Combination With Antineoplastic Mitotane Improved the Bacterial Killing Against Polymyxin-Resistant Multidrug-Resistant Gram-Negative Pathogens

Abstract: Due to limited new antibiotics, polymyxins are increasingly used to treat multidrug-resistant (MDR) Gram-negative bacteria, in particular carbapenem-resistant Acinetobacter baumannii, Pseudomonas aeruginosa, and Klebsiella pneumoniae. Unfortunately, polymyxin monotherapy has led to the emergence of resistance. Polymyxin combination therapy has been demonstrated to improve bacterial killing and prevent the emergence of resistance. From a preliminary screening of an FDA drug library, we identified antineoplastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 49 publications
0
38
1
1
Order By: Relevance
“…Taking all in vitro results, in vivo results, and previously reported data into consideration, we further studied PFK-158 as a promising potentiator of colistin. Unlike the other potentiators reported previously (7,11,16,17,21), colistin in combination with PFK-158 showed a constant killing effect, which eliminated the bacteria below the detection limit in time-kill studies. This finding reminded us that PFK-158 might have a unique mechanism of action.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Taking all in vitro results, in vivo results, and previously reported data into consideration, we further studied PFK-158 as a promising potentiator of colistin. Unlike the other potentiators reported previously (7,11,16,17,21), colistin in combination with PFK-158 showed a constant killing effect, which eliminated the bacteria below the detection limit in time-kill studies. This finding reminded us that PFK-158 might have a unique mechanism of action.…”
Section: Discussioncontrasting
confidence: 59%
“…However, the discovery of the mcr-1-carrying plasmid in 2015 broke the last barrier between superbugs and humans, and new therapies or drugs are urgently needed. Although several nonantibiotics that are synergistic with polymyxins were reported recently, most of them were evaluated in vitro (10,(16)(17)(18), and only a few compounds have been evaluated in animal models (11,(19)(20)(21). Hence, we screened a clinical compound library to search for new compounds that can potentiate colistin efficacy and discovered that one class of chemicals, PFK-158 and its analogs, could fight against polymyxin-resistant pathogens when used together with colistin.…”
Section: Discussionmentioning
confidence: 99%
“…The use of synergistic combinations of antibiotics with FDA-approved nonantibiotics has been proposed as a promising alternative to improve the clinical efficacy of polymyxins against these problematic MDR Gram-negative pathogens (13,(15)(16)(17)(18)(19). To date, a number of studies have shown that polymyxin B in combination with FDA-approved nonantibiotics drugs (e.g., ascorbic acid [20], benserazide [20], chloroxine [20], closantel [16], loperamide [21], tamoxifen [17], tegaserod [20], mitomycin C [20], mitotane [19], ivacaftor [15], and silver nanoparticles [18]) display synergistic killing activity against MDR Pseudomonas aeruginosa and Acinetobacter baumannii. However, only several studies investigated the efficacy of polymyxin combinations with nonantibiotic drugs against NDM-producing MDR K. pneumoniae (13,17,18).…”
mentioning
confidence: 99%
“…Polymyxins are lipopeptide antibiotics with bactericidal activity against Gram-negative bacteria that work by disrupting the cell membrane via both hydrophobic and electrostatic interactions [17]. Tran et al screened FDA approved drugs to identify potential synergistic candidates with polymyxins for MDR Gram-negative bacteria eradication [24]. They identified a non-antibiotic drug-mitotane (steroidogenesis inhibitor and cytostatic antineoplastic medication) as a potential candidate for combination therapy with polymyxin B against Gram-negative bacteria such as carbapenem-resistant P. aeruginosa, A. baumannii, and K. pneumoniae (Table 1) [24].…”
Section: Combination Therapy I: Increases Membrane Permeabilitymentioning
confidence: 99%
“…Tran et al screened FDA approved drugs to identify potential synergistic candidates with polymyxins for MDR Gram-negative bacteria eradication [24]. They identified a non-antibiotic drug-mitotane (steroidogenesis inhibitor and cytostatic antineoplastic medication) as a potential candidate for combination therapy with polymyxin B against Gram-negative bacteria such as carbapenem-resistant P. aeruginosa, A. baumannii, and K. pneumoniae (Table 1) [24]. It is hypothesized that increased permeability of the outer membrane caused by polymyxin B may lead to the entry of mitotane into the bacterial cells, however, the mechanism by which mitotane inhibits the bacterial pathogen growth remains unclear.…”
Section: Combination Therapy I: Increases Membrane Permeabilitymentioning
confidence: 99%